یہود کے نَحْنُ اَبْنٰۗؤُا اللّٰهِ وَاَحِبَّاۗؤُه ہونےکادعوی اوراس کی تردیدمختلف تفاسیرکی روشنی میں تجزیاتی مطالع: THE JEWS' CLAIM THAT (WE ARE THE CHILDREN OF ALLAH AND HIS BELOVED) AND ITS DENIAL: AN ANALYTICAL STUDY IN THE LIGHT OF DIFFERENT INTERPRETATIONS (Contemporary Journal of Social Science Review, 2025)
The history of the divine religions is a witness to the fact that whenever a nation considered itself superior on the basis of mere ethnic, religious or historical affiliation, it resulted in intellectual deviation and practical decline. This claim of the Jews, “We are the children of Allah and His beloved,” is a prominent example of this mental and belief deviation, through which they declared themselves to be the specially chosen and beloved group of Allah Almighty. This claim not only limited their religious consciousness but also weakened their sense of moral responsibility and accountability. The Holy Quran, while explaining this concept with great clarity and wisdom, strongly refuted it and made it clear that the criterion of affiliation with Allah Almighty is not a mere claim or attribution, but practical commitment, obedience and piety. In this context, the study of this subject is of great importance for a correct understanding of Islamic beliefs and for creating a balance in religious thought. The Holy Quran’s method of refuting this claim of the Jews is not merely argumentative but corrective and educational, aiming to draw man towards realistic thinking and self-accountability. Various interpretations of the Quran explain that this concept of “sonship” and “belovedness” was actually the result of a misunderstanding of the attributes, justice and wisdom of Allah Almighty. According to the commentators, if a nation is considered unconditionally beloved and saved, then the importance of adherence to the Sharia, moral responsibility and righteous deeds ceases. Therefore, the Quran presented a universal principle in contrast to this claim that the standard of excellence in the eyes of Allah is piety. This article will analyze this statement of the Jews in the light of various exegetical literature of the Quran.